Digital Religion, Modern Society and the Construction of Digital Theology - Zaluchu, Sonny Eli (2024)
Using a literature approach and a sociology of religion perspective, this research discusses the concept and phenomenon of digital religion in modern society. It is concluded that digital religion is not just the phenomenon of online religious practice for spiritual purposes but rather the extension of traditional religion into a new culture due to the digitalisation of society. The networked nature of modern society has a significant impact on the way people shape their experience of religiosity. Dialogue about God takes place in new forms as a form of cyber-theology. The results of this study challenge further research to see the extent to which people build their faith when spiritual experiences change into digital forms.
Keywords: digital theology; online worship; sociology of religion; network society; digitalisation; Modern Society; cyber-theology; Digital Religion